Sir Gawain and the Green Knight: Meanings and Interpretations - Jakovljević, Mladen M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The importance of Sir Gawain and the Green Knight for the history of English literature lies in the richness of its story and language, complexity of its structure and the poet’s virtuosity. Another reason why it continues to attract and sustain broad interest of numerous theorists from around the world arises from the inspiration it provides for new interpretations, fuelled with its author’s ambivalent attitude towards the ideals of romance and the ideals of his time in general, which brings it closer to the attitudes prevailing in contemporary literature. The potentials of this romance - veiled in mystery, challenging to readers, and deeply inspiring to contemporary authors - are owed to the features that contemporary English and Serbian fantasy borrows from medieval literature: a mythical past combined with (usually medieval) history, then a commixture of natural, supernatural and divine, as well as a blend of pre-Christian and Christian motifs. Accordingly, it is worth encouraging closer acquaintance of Serbian readers and theorists with its numerous values through verse translation and further, deeper analyses in the Serbian language.